Temperature Evaluation of Heat Transferring Body while Preparing Temperature Chart of Heating Technologies and Metal Thermal Treatment - A. P. Nesenchuk; T. V. Ryzhova; O. F. Kraetskaya; S. S. Kovaliov; A. V. Begliak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems pertaining to temperature evaluation of a heat transferring body in the operational space of high temperature installations. A formula for evaluation of this temperature has been written down in the paper. Calculation of a heating transferring body (furnace) makes it possible to realize temperature chart parameters in the plant heating technologies and steel thermal treatment.